DIAGNOSTICO DE LA FIEBRE TIFOIDEA POR AGLUTINACION SELECTIVA - RUIZ CASTANEDA, MAXIMILIANO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1942)
Based on immunologic differences found between endemic and epidemic typhus strains, some authors recommend the production of epidemic vaccines as means of practical protection against the infection Such vaccines have little if any value against "murine"
REV MEX MED
Keywords: DIAGNOSTICO, FIEBRE, TIFOIDEA, AGLUTINACION; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS